Wireless Multipurpose Robot - Agarwal, Ishita; Priyalakshmi, B; Mundhra, Yosha; Pathak, Misha (International Journal of Engineering and Technology, 2018)
There are a number of situations in which it isn't always viable for a human operator to do an activity on their own, due to a level of threat or involved. The threat can be anything like a fire may begin in some factory or in some faraway locality. For example, in the cotton generators, gasoline storehouses, and so on, leakages in the electric field may lead to massive harm, inflicting heavy losses financially and additionally destroying regions round it. Instead of compromising human lives, it is advisable to hire robot structures for performing difficult duties. Robotic systems are far advanced in ensuring the accuracy of the device beneath unfavorable instances where a human may lose his/her life. Our objective is, making Â a fire extinguishing robot with embedded gadget along with aÂ wireless Bomb Disposal robot. The bomb technician controls the robot using a software at control web page. Robot is manufactured for discovering the fire, earlier than something goes out of manage, and sooner or later operate with fireplace-combatants decreasing the risk for humans.